1980
DOI: 10.1113/jphysiol.1980.sp013366
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary intake of sodium chloride on sugar and amino acid transport across isolated hen colon

Abstract: SUMMARY1. Using the isolated mucosa from the colon ofthe adult hen, transport of galactose, leucine and lysine was studied through measurements of influx across the brushborder membrane, unidirectional transmucosal fluxes, and of steady-state mucosal uptake.2. In hens maintained on a NaCl rich diet influx of galactose, leucine and lysine were saturable processes with well defined values for Jmax and Kt. All three substances were actively transported across the epithelium and accumulated in the mucosal tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…For the low Na colon the results indicate that Na coupled transport of sugars and lysine cannot be accomplished. Lind, Munck & Olsen (1980) have confirmed the validity of these interpretations. In a variety of colonic mucosae availability of glucose to the tissues plays a crucial role for the maintenance of the I8, (Binder & Rawlins, 1973;Thompson & Dawson, 1978;Frizzell, Koch & Schultz, 1976).…”
Section: Discussionsupporting
confidence: 63%
“…For the low Na colon the results indicate that Na coupled transport of sugars and lysine cannot be accomplished. Lind, Munck & Olsen (1980) have confirmed the validity of these interpretations. In a variety of colonic mucosae availability of glucose to the tissues plays a crucial role for the maintenance of the I8, (Binder & Rawlins, 1973;Thompson & Dawson, 1978;Frizzell, Koch & Schultz, 1976).…”
Section: Discussionsupporting
confidence: 63%
“…The changes in transepithelial Na¤ movements according to dietary NaCl are correlated with changes in plasma aldosterone (Skadhauge, 1993). The intestinal co-transport of Na¤ with certain nutrients is also sensitive to the NaCl status; thus, Lind et al (1980) observed that glucose-and amino acid-induced short-circuit current across the rectum was abolished in NaCl-depleted chickens. It was later demonstrated that rectal enterocytes lose the capacity to accumulate hexoses (Jaso et al 1995) due, among other factors, to a decrease in apical SGLT1 expression (Bindslev et al 1997;Garriga et al 1998).…”
mentioning
confidence: 99%
“…All regions of the lower intestine also contribute to the resorption of ureteral electrolyte and fluid (Skadhauge, 1993). Furthermore, the proximal caecum and the rectum can also absorb Na¤ cotransported with glucose and amino acids (Lind et al 1980;Moret o & Planas, 1989;Ferrer et al 1994b;Amat et al 1999). All these functions are affected by the NaCl status of the animal since restriction of Na¤ intake results in adaptive regulation, especially in the lower intestine, where there is a marked increase in the apical epithelial Na¤ channel (ENaC; Goldstein et al 1997) and the Na¤-H¤ exchanger (NHE2; Donowitz et al 1998) activities, and in the short-circuit current (Thomas & Skadhauge, 1982;Amat et al 1988).…”
mentioning
confidence: 99%
“…However, the results of our experiment indicate that increased amino acid concentration not always caused increased absorption. The presence of glucose (Olszewski, 1975) or sodium and potassium ions (Robinson et al, 1973;Lind et al, 1980;Munck, 1981) were found to play important role in the absorption of some amino acids from the caecum or colon of sheep, dog or chicken. Such data support the active or facilitated character of the absorption process.…”
Section: Contrary To the Results Ofmentioning
confidence: 99%